2005
DOI: 10.1158/1535-7163.mct-05-0146
|View full text |Cite
|
Sign up to set email alerts
|

Transcript profiling in peripheral T-cell lymphoma, not otherwise specified, and diffuse large B-cell lymphoma identifies distinct tumor profile signatures

Abstract: To glean biological differences and similarities of peripheral T-cell lymphoma-not otherwise specified [PTCL-NOS] to diffuse large B-cell lymphoma (DLBCL), a transcriptosome analysis was done on five PTCL-NOS and four DLBCL patients and validated by quantitative real-time reverse transcription-PCR on 10 selected genes. Normal peripheral blood T cells, peripheral blood B cells, and lymph node were used as controls. The resultant gene expression profile delineated distinct ''tumor profile signatures'' for PTCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 59 publications
4
57
0
Order By: Relevance
“…In particular, BCL2A1 developmentally regulated in B and T cells, where it sustains the viability of T lymphoblasts (26,38). In cancer cell lines, BCL2A1 is overexpressed in certain human epithelial and hematopoietic malignancies such as diffuse large B cell lymphoma and B cell chronic lymphocytic leukemia (39,40). Using multiple approaches to inactivate ALK signaling in ALCL cells, we demonstrated that BCL2A1 is a specific NPM-ALK-regulated gene.…”
Section: Discussionmentioning
confidence: 92%
“…In particular, BCL2A1 developmentally regulated in B and T cells, where it sustains the viability of T lymphoblasts (26,38). In cancer cell lines, BCL2A1 is overexpressed in certain human epithelial and hematopoietic malignancies such as diffuse large B cell lymphoma and B cell chronic lymphocytic leukemia (39,40). Using multiple approaches to inactivate ALK signaling in ALCL cells, we demonstrated that BCL2A1 is a specific NPM-ALK-regulated gene.…”
Section: Discussionmentioning
confidence: 92%
“…Syk has been suggested as a potential therapeutic target for PTCL by Mahadevan et al, 19 but previous data on Syk expression in T-cell lymphomas are limited and somewhat conflicting. A small study found Syk in only 2/19 PTCLs by IHC, including 1/8 PTCL-U and 1/1 mycosis fungoid (weak staining).…”
Section: Resultsmentioning
confidence: 99%
“…The GIST-R (0.5 mM IM) cell line was treated with MP470 (1 mM) for 6 and 24 h. Total RNA was extracted from GIST-S, GIST-R (0.5 mM IM) and MP470-treated GIST-R at 6 and 24 h utilizing the RNeasy Mini Kit (Qiagen, CA, USA) as described previously (Mahadevan et al, 2005b). …”
Section: Cell Morphology Analysismentioning
confidence: 99%